2022
DOI: 10.1021/acs.joc.2c00555
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyrrolo[2,1-a]isoquinolinium Salts from 1-Pyrrolines and Alkynes via Rhodium-Catalyzed C–H Functionalization/N-Annulation Tandem Reaction

Abstract: A convenient synthesis of pyrrolo­[2,1-a]­iso­quino­linium salts from 1-pyrrolines and alkynes through rhodium-catalyzed C–H functionalization/N-annulation tandem reaction is described. The protocol features a good substrate tolerance, mild reaction conditions, and high yields of target products. Exploration of the alkyne scope unexpectedly revealed a novel labile functional group-promoted rhodium-catalyzed C–H functionalization/C-annulation/elimination cascade reaction of 1-pyrrolines with electron-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In addition, a single crystal of good quality was obtained from 4a for X-ray analysis (Figure 2). Based on the literature precedents [23,[37][38][39] and the results obtained above, the mechanism of the transformation outlined in Scheme 4 is proposed. Initially, the rhodium dimer complex [Cp*RhCl2]2 is easily converted into the catalytically active Cp*Rh III (OAc) species via dissociation and consecutive ligand exchange.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a single crystal of good quality was obtained from 4a for X-ray analysis (Figure 2). Based on the literature precedents [23,[37][38][39] and the results obtained above, the mechanism of the transformation outlined in Scheme 4 is proposed. Initially, the rhodium dimer complex [Cp*RhCl2]2 is easily converted into the catalytically active Cp*Rh III (OAc) species via dissociation and consecutive ligand exchange.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, the rhodium dimer complex [Cp*RhCl2]2 is easily converted into the catalytically active Cp*Rh III (OAc) species via dissociation and consecutive ligand exchange. Precomplexation to the directing dehydropirrolidine moiety is followed by the cleavage of ortho-C-H bond of phenyl Based on the literature precedents [23,[37][38][39] and the results obtained above, the mechanism of the transformation outlined in Scheme 4 is proposed. Initially, the rhodium dimer complex [Cp*RhCl 2 ] 2 is easily converted into the catalytically active Cp*Rh III Based on the literature precedents [23,[37][38][39] and the results obtained above, the mechanism of the transformation outlined in Scheme 4 is proposed.…”
Section: Resultsmentioning
confidence: 99%
“…These unique aza-heterocycles turned out to be fruitful reactive intermediates in diverse synthetic transformations. 16 Among the latter, the acid-catalyzed reactions of 5-hydroxypyrrolines and 3 H -pyrroles with C-, N-, O- and S-nucleophiles are of particular value as a tool for the construction of rare functionalized pyrrolines. 17 Herein we report our observations on the diastereoselective synthesis of tetrahydropyrrolo[1,2- d ]oxadiazoles from thus-synthesized functionalized Δ 1 -pyrrolines and in situ generated nitrile oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a relatively high price, rhodium‐metal complexes continue to be the catalysts of choice due to their outstanding efficiency in building diverse polycyclic heteroaromatic compounds in a single step from simple starting materials. In our recent study [9] we demonstrated that this already common synthetic tool may be successfully extended to the synthesis of dihydropyrrolo[2,1‐ a ]isoquinolinium salts from alkynes and 1‐pyrrolines bearing labile functional group (Scheme 1c). Using this knowledge as a starting point, we suggested that hitherto unknown chemical transformation between aryl‐substituted 2 H ‐ and 3 H ‐pyrroles and unactivated alkynes, which involves formal nucleophilic interaction of the nitrogen lone electron pair with electrophilic carbon‐carbon triple bond of alkyne, can be realized through rhodium catalysis.…”
Section: Introductionmentioning
confidence: 99%